Peningkatan Literasi Keuangan Bagi Penerima Program Keluarga Harapan Di Kecamatan Muara Bangkahulu Kota Bengkulu - Merri Anitasari; Hutapia Hutapia; Benardin Benardin; BIE Indraswanti (Universitas Dehasen Bengkulu, 2026)
Program Keluarga Harapan is a strategic government program aimed at reducing poverty through conditional social assistance. However, the effectiveness of this assistance depends heavily on the ability of beneficiaries to manage their finances. This community service activity aims to improve the financial literacy of families receiving Program Keluarga Harapan in Muara Bangkahulu District, Bengkulu City.The methods used include outreach, interactive training, simulations, and individual mentoring in developing family financial plans. With a participatory, educational approach, participants are expected to be able to manage their assistance more productively and sustainably.The results of this activity include an increased understanding of simple financial management, an increased savings culture, and a reduced use of assistance for consumer needs. This program is expected to contribute to poverty alleviation efforts and increase the economic independence of Program Keluarga Harapan recipient families.